Phylogeny and re-definition of the genus Melanophora (Diptera: Rhinophoridae), with description of a new species from Sardinia - Cerretti, Pierfilippo; Pape, Thomas (Zootaxa, 2009)
A cladistic analysis of the genus Melanophora Meigen, 1803 (type-species: Musca grossificationis Linnaeus, 1758 [= Musca roralis Linnaeus, 1758]) is presented and the generic delimitation is critically redefined. The nominal genus-group taxon Bequaertiana Curran, 1929 (type-species: Bequaertiana argyriventris Curran, 1929) is synonymised with Melanophora Meigen syn. nov. The following new combinations are proposed: Melanophora argyriventris (Curran, 1929) comb. nov. and Melanophora basilewskyi (Peris, 1957) comb. nov. Melanophora chia sp. nov. from SW Sardinia is described, illustrated and compared with the other known species of the genus. The male of Melanophora asetosa Kugler, 1978 is described for the first time. Melanophora basilewskyi (Peris, 1957) is recorded from Kenya for the first time.